Parent-child relations in families that bring up down syndrome children - Suhonos, O. (Journal of Education, Health and Sport, 2021)
Down syndrome children need special attention. As long as the illness is often accompanied by mental disorders, there should be an individual approach to child in upbringing and education. This compels parents to adjust their rhythm of life in accordance with child's needs. Difficulties in raising a child with special needs can lead to a deterioration in the attitude of parents towards the child. This comes out in the behavior of parents and leaves an imprint on the psychological state of the child, his character and subsequent life. Materials and methods: 97 Down syndrome children were examined. All patients met the inclusion criteria. The patients' parents gave informed consent to the participation in the study. Down syndrome in children has been genetically verified. Patients were divided into two groups according to the criterion of ability to verbal communication: group 1 (G1) included 77 children capable of verbal communication, group 2 (G2) – 20 children who did not speak. Individualization in the most of both groups respondents was at an average level, which indicated sufficient parents’ acceptance of the individual characteristics of the child, sufficient attention to his interests, satisfaction with the time spent together. Cooperation did not show statistically significant differences in G1 and G2. The average score on this indicator did not differ in both groups (6.87±1.13 for G1, 6.75±1.10 for G2). Statistically significant difference between G1 and G2 was found in symbiosis (4.25±1.43 points against 5.10±1.55 points, respectively). Authoritarianism in G1 was 3.27±1.26 points, in G2 – 4.05±1.60 points, which corresponds to the average level of severity and means achieving a balance between giving the child freedom of action and the establishment of restrictions. Disability in G1 and G2 was 2.43±1.40 and 2.90±1.77, respectively, which corresponds to a low level of its severity: parents of Down syndrome children are generally not inclined to increase the defects of their children, regardless of their language skills.